Frontotemporal dementia: impact of P301L tau mutation on a healthy carrier. Issue 11 (15th October 2004) - Alberici, A; Gobbo, C; Panzacchi, A; Nicosia, F; Ghidoni, R; Benussi, L; Hock, C; Papassotiropoulos, A; Liberini, P; Growdon, J H; Frisoni, G B; Villa, A; et al.
Abstract : Frontotemporal dementia (FTD) is the second commonest form of dementia after Alzheimer's disease, but its clinical and biological features are less well known. To uncover its earliest signs, we studied the main clinical, neuroimaging, and biochemical findings in an asymptomatic carrier from a three generation FTD family, bearing the P301L pathogenic mutation in the tau gene. Except for selective impairment on the Verbal Fluency Test for letters, all cognitive tests were normal. The brain computed tomography scan was normal, but the brain single photon emission computed tomography and statistical parametric mapping (SPECT-SPM) scan revealed bilateral frontal lobe hypoperfusion. Levels of total tau, 181P-tau, and Aβ1-42 in the cerebrospinal fluid were increased compared with control values. We conclude that detection of these distinctive abnormalities should improve early diagnostic accuracy for FTD and help distinguish it from Alzheimer's disease.